Paediatric inflammatory bowel disease in Scotland: a continued rise in incidence. (29th September 2015) - Cameron, F; Henderson, P; Hansen, R; Gerasimidis, K; Reynish, E; Drummond, H; Bisset, WM; Satsangi, J; Russell, RK; Wilson, DC
Abstract : Introduction: The incidence of early-onset inflammatory bowel disease (IBD) is high in Europe and North America with numbers rising in recent decades. An accurate indication of the current incidence and temporal trends experienced by a whole population is useful in understanding possible aetiological factors and is essential for the planning of future specialist healthcare provision. Method: This study reports the incidence of early-onset IBD within the Scottish population over a 6-year period (2003–2008), comparing the incidence and demographic attributes to previous figures. Three paediatric gastroenterology networks provide care for all paediatric IBD patients in Scotland. Retrospective data regarding incident cases of IBD diagnosed <16 years old were collected using a centrally coordinated database. Duplicates and diagnoses outwith Scotland were excluded. General Register Office for Scotland population statistics were used to calculate incidence. Statistical comparisons were made by Mann-Whitney U test. Results: During the study period 430 patients <16 years were diagnosed with IBD in Scotland giving an overall incidence of 7.7/100 000/year. The incidence of Crohn's disease (CD) was 4.7/100 000/year, ulcerative colitis (UC) 2.0/100 000/year and inflammatory bowel disease unspecified (IBDU) 1.0/100 000/year. When compared with previous data from 1990–1995, significant rises in the incidence of IBD from 4.4/100 000/year (p=0.002) and CD from 2.8/100 000/year (p=0.002) were seen. The rise in UC from 1.6/100 000/year was not significant (p=0.13). The median age at diagnosis between 2003–2008 was 11.8 years for IBD and UC, and 11.9 years for CD. When compared with 1990–1995 data, there was a significant decrease in the age at diagnosis of CD from 12.8 yrs (p=0.009), but not in UC from 12.3 years (p=0.49). Conclusion: The number of Scottish children diagnosed with IBD continues to rise with the rates of IBD and CD rising significantly by 70% and 61%, respectively. Although UC has risen by 25%, this was not significant. This continuing rise has clear implications for the health of Scotland's children and the local provision of specialist healthcare. A greater understanding of the changing demographic of early-onset IBD may give us clues as to the aetiology of this chronic condition and aid future disease prevention measures.